Methyl Cellulose Based Sustained Release Thermosensitive in situ Fast Gelling Ocular Delivery of Ketorolac Tromethamine - Bhowmik, Manas; Das, Sanchita; Sinha, Jaydeep; Bag, Swarnendu; Chattopadhyay, Dipankar; K. Ghosh, Lakshmi (Asian Journal of Chemistry, 2010)
The purpose of this study is to develop methyl cellulose (MC) based in situ gelling formulations of ketorolac tromethamine (KT) for enhan-cing its ocular bioavailability. The gelation temperature of 1 % w/v MC solution was 60 ºC. Sodium chloride was added to reduce the gelation temperature of MC solution below physiological temperature, i.e., 37 ºC. The effect of NaCl concentration on the rheological property and drug release profile of prepared formulations were examined. It was observed that 5-7 % w/v NaCl lowered the gelation temperature below 37 ºC and the solution was free flowing liquid at 25 ºC for proper instillation to the eye as drop (s) and gave sustain drug release profile. In an attempt to increase drug release time by increasing viscosity of gel at 37 ºC without compromising the in situ gelation capability, hydroxy propyl methyl cellulose (HPMC K15 M) was added, replacing MC that gave finally 1 % w/v polymer (MC and HPMC mixture) solution contai-ning 0.5 % w/v KT. The viscosity and drug release profile of prepared formulations containing HPMC were evaluated. The highest viscosity at 37 ºC and slowest drug release was obtained from MC:HPMC::2:1 solution containing 7 % w/v NaCl.